The Role of Academic Library and Librarians in Enhancing Entrepreneurship in Nigeria (2019)
There is a great need to extend library profession base on the fast growing needs of employment in the country as at today. To reduce the unemployed rate that has reached an alarming stage which is due to economic recession and constant decline in industry which would have lead to the drive of the economy of the nation at large. The present economic realities and the challenges in labour market in Nigeria as well as the increase in unemployment of our graduates also justify the need to equip undergraduates with the basic entrepreneurial skills and accurate knowledge that would enable them to be self-employed after graduation. Moreover, users of library no longer see the need to visit the library because library services are not attractive and packaged in ways that will make them visit the library. There is therefore, the need to make library services attractive; this will require that teachers or lecturers need to infuse entrepreneurial courses in their curriculums irrespective of the courses that they teaches at institutions of higher learning. The acquisition of entrepreneurial texts books both hard copies and soft copies should be available for the use of both students and academic staff. Hence library services need to engage in entrepreneurship education in academic school curriculum will greatly enhance entrepreneurial knowledge and skills which will prepare graduate students for the challenge of the labour market and make them to be self employed in the long run.